2011
DOI: 10.1111/j.1524-4725.2010.01847.x
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Noncultured Melanocyte Transplantation for Stable Vitiligo: Can Suspending Autologous Melanocytes in the Patients' Own Serum Improve Repigmentation and Patient Satisfaction?

Abstract: Results of noncultured melanocyte transplantation can be improved significantly more by suspending the melanocytes in the patients' autologous serum than in normal saline. This could be an important innovation in the surgical management of patients with stable vitiligo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 18 publications
1
49
0
1
Order By: Relevance
“…The overall reported efficacy of NB‐UVB phototherapy in attaining >75% repigmentation ranged from 12.5% to 75%, that too after a period of 1 year . The similar outcome can be achieved within 4 months by NCES as per the published clinical trials . Hence, NCES is an efficacious alternative to phototherapy in stable vitiligo.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…The overall reported efficacy of NB‐UVB phototherapy in attaining >75% repigmentation ranged from 12.5% to 75%, that too after a period of 1 year . The similar outcome can be achieved within 4 months by NCES as per the published clinical trials . Hence, NCES is an efficacious alternative to phototherapy in stable vitiligo.…”
Section: Discussionmentioning
confidence: 69%
“…They introduced PBS, a buffer solution commonly used in biological research, in place of melanocyte culture media and also used it to wash off excess trypsin thus circumventing the use of expensive trypsin inhibitor. Sahni et al . have demonstrated improvement of repigmentation outcome by suspending the melanocytes in the patients’ own serum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one study reported QoL as the primary outcome measure . There was only one study where the investigators found a statistically significant result for this outcome, which showed a result in favour of a melanocyte suspension suspended in the patient's own serum, compared with suspension in normal saline ( P = 0·005). However, there were insufficient data to enable us to perform an analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Efforts were made to improve performance of noncultured cell transplantation. In one example, the use of autologous serum for melanocyte resuspension resulted in significantly better repigmentation supported by better improvement when judged based on Dermatology Quality of Life Index score . Khodadadi et al.…”
Section: Resultsmentioning
confidence: 99%